Clumped isotope analysis of zoned calcite cement, Carboniferous, Isle of Man - Dickson, John Anthony Dawson; Hodell, David A; Swart, Peter K; Lu, Chaojin; Mleneck‐Vautravers, Maryline J; Rolfe, James E (Wiley, 2023)
Abstract Sequential analyses of δ 13 C, δ 18 O and Δ 47 values of calcite and dolomite deposited in millimetre‐sized cavities are reported from the Ronaldsway Member packstones, Isle of Man. The Ronaldsway brachiopods have δ 13 C values of ca +2.3‰ and δ 18 O values of ca −7.2‰; carbon is like predicted Carboniferous values, while oxygen values are more negative. The brachiopods show preserved microstructure but have marginal alteration and a streaky cathodoluminescence pattern. Crinoid ossicles have δ 13 C values of ca +2.3‰ and one with a δ 18 O value of ca −3.1‰, compatible with Carboniferous marine precipitates; three samples have δ 18 O values of ca −6.5‰ and are 18 O‐depleted. Calcite stages 1 and 2 have δ 13 C values ca +3.2‰ and δ 18 O values ca −2.5‰, compatible with Carboniferous sea water. Stage 1 and 2 have non‐luminescent to orange CL zones. Stage 1 and early stage 2 contain red luminescent dolomite micro crystals generated during Mg calcite stabilisation. The Δ 47 values for stage 1 and 2 cements indicate temperatures of 86 and 105°C that occurred after the stabilisation of Mg calcite. Stage 3–8 zoned cements preserve their original growth surfaces and their δ 13 C and δ 18 O values suggest precipitation during burial and exhumation. The Δ 47 values of the brachiopods and crinoids indicate temperatures between 85 and 140°C indicating they were either recrystallised at high temperatures or affected by solid state reordering. To evaluate these alternatives two quantitative models, water–rock reaction and reordering models are performed. The allochems and cements are progressively altered by porewater towards the fluid‐buffered behaviour. The quantitative evaluation of calcite and dolomite solid‐state reordering suggests the elevated clumped isotopic temperatures are produced by interaction with hydrothermal fluids. This study improves understanding by applying previously untried techniques; further Δ 47 data and quantifying elemental variations would help further interpretation but the poorly documented post‐depositional history is a drawback.
Keywords: 37 Earth Sciences; 3705 Geology